2018
DOI: 10.5455/medarh.2018.72.330-334
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Acinetobacter Species in the Hospital Environment

Abstract: Introduction:Acinetobacter species is associated with health care associated infections especially in patients on respiratory therapy equipment and indwelling catheters. They are becoming increasingly drug resistant. The knowledge of the prevalence and pattern of antimicrobial susceptibility pattern of Acinetobacter spp. is important.AimsThe study is undertaken to estimate the prevalence rate, risk factors and antimicrobial resistance pattern of isolates. in Acinetobacter spp. from various clinical samples.Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 15 publications
(16 reference statements)
3
25
2
Order By: Relevance
“…The overall prevalence of MDR among the isolates was 71.6% which is comparable with a report from Saudi Arabia (74%) [ 19 ] and Bosnia and Herzegovina (78.4%) [ 20 ]. However, the current finding was higher than the study conducted in Jimma which isolated the MDR Acinetobacter species from wound specimen at a rate of 57.2% [ 21 ], and in Iran at a rate of 56.7% [ 22 ].…”
Section: Discussionsupporting
confidence: 83%
“…The overall prevalence of MDR among the isolates was 71.6% which is comparable with a report from Saudi Arabia (74%) [ 19 ] and Bosnia and Herzegovina (78.4%) [ 20 ]. However, the current finding was higher than the study conducted in Jimma which isolated the MDR Acinetobacter species from wound specimen at a rate of 57.2% [ 21 ], and in Iran at a rate of 56.7% [ 22 ].…”
Section: Discussionsupporting
confidence: 83%
“…Acinetobacter can be isolated from multiple parts of health human body [18] and reused medical devices. It could be found in many health care environment and causes human colonizer in hospitals, especially in patients with mechanical ventilation in intensive care units and indwelling catheters [19]. A retrospective study in an adult ICU in a tertiary care hospital has showed that most frequently isolated organism was Acinetobacter baumannii [20].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary PDR isolates were resistant "to all antibiotic groups except tigecycline and colistin" Owrang M et al 2018 [237] "All of the isolates were pandrug resistant A. baumannii and the lowest resistance rates were observed toward minocycline and amikacin (93.33% in both) and trimethoprim/sulfamethoxazole (92.38%)." Rebic V et al 2018 [238] Polymyxin not tested in most isolates. All isolates with susceptibility testing to colistin available were susceptible.…”
Section: The Patient Died With Persistent Bacteremiamentioning
confidence: 99%